EFFECT OF POSTPARTUM PERIOD ON SUPEROVULATORY RESPONSE IN CROSSBRED AND INDIGENOUS CATTLE - PATEL, D V; BHALODIA, S D; CHAUDHARI, N N; PATIL, S R; BHATOL, J G; SHRMA, H C; DEVANAND, C P (The Indian Journal of Animal Reproduction, 2023)
Large numbers of factors are responsible for the superovulatory response in bovines and one of them iscalving to flushing interval. Milking animals are under considerable stress due to negative energy balance postcalvingwhich considerably affects the reproductive system. Sizeable number of crossbred and indigenous donorcows were superovulated and flushed at different stages post-calving, i.e. 300 days. The pooled mean total embryos recovered were 7.57, 7.29, 7.98 and 4.31 , respectively. Thecorresponding mean viable embryos recovered were 2.64, 4.90, 4.69 and 3.88, respectively for the four postpartumperiods. Although there was no significant difference with respect to total embryo recovery, there was non-significantlyless number of viable embryo recovery in < 90 days group compared to all other groups. Superovulatory responsewith recovery of total and viable embryos per donor was better at all intervals postpartum in crossbreds as comparedto indigenous cows. In both, crossbred and indigenous animals, the viable embryo recovery rate was low comparedto the total embryo recovery rates when the donors were flushed before 90 days post-calving.
Keywords: Calving; Flush; Superovulation; Responses